Effects of non-uniform pore pressure field on hydraulic fracture propagation behaviors. (November 2019) - Gao, Qi; Han, Songcai; Cheng, Yuanfang; Yan, Chuanliang; Sun, Yuanwei; Han, Zhongying
Highlights: A poroelastic model is proposed to study HF growth in non-uniform pore pressure field. The effects of five-spot well pattern on HF growth are detailedly illustrated. The effects of four operational parameters on HF growth are analyzed. Results provide new insights for better understanding HF propagation in the field scale. Abstract: Hydraulic fracturing is one of the key technologies to stimulate oil and gas production in low-porosity and low-permeability reservoirs. Thus, understanding the hydraulic fracture (HF) propagation behaviors is of great significance for optimizing the fracturing design. It is usually assumed that HF tends to take a straight path in a symmetric stress and uniform pore pressure field. However, much more complex stress and pore pressure distribution could be encountered during the fracturing treatment as a result of long-time fluid injection and production in the reservoir. In this paper, considering the arrangement of five-spot well pattern, the effects of unsymmetric stress and non-uniform pore pressure distribution on HF growth is investigated using the cohesive zone method (CZM) and extended finite element method (XFEM). The interesting results indicate that in-situ stress and pore pressure distribution are gradually altered due to fluid injection and production, which affects subsequent HF growth. And in the reservoir developed by five-spot well pattern, HF tends to initially propagate along a straight line with fracture growth rate gradually decreasing and then prefers to extend towards the nearby injection well with fracture growth rate gradually increasing when there exists an intersection angle ( 0 ° < θ < 45 ° ) between the direction of well arrays and minimum horizontal stress orientation. When θ equals 0 ° or 45 °, HF will extend along a straight line without curving. The results also show that a larger water injection pressure leads to a greater fracture deviation angle, but a larger fracturing fluid injection rate and a larger water injection well distance results in a smaller fracture deviation angle. Moreover, the influence of fracturing fluid viscosity on fracture deviation angle can be ignored.